An Analysis of English Classroom Interaction Pattern at Eleventh Grade of SMKN 4 Kerinci Based On El Hanafi Theory - Mike Nurmalia Sari; Pretty Elisa Ayu Ningsih; Arema Novita (Universitas Jabal Ghafur, 2023)
This research aimed at investigating the classroom interaction patterns on English classes at Eleventh grade of SMKN 4 Kerinci. This research is a descriptive research. The subjects of the research were four English teachers who taught grade XI, they are Teknik Bisnis Sepeda Motor class, Bisnis Daring Dan Pemasaran class, Otomatisasi Tata Kelola Perkantoran class, and Multimedia class. To see the pattern of interaction, theory from El Hanafi was used. The classification of classroom interaction are: (1) teacher-student interaction with one-way traffic interaction, (2) teacher-student interaction with two-way traffic interaction, (3) teacher-student interaction with multi-way traffic interaction, and (4) student-student interaction pattern. Each teacher was recorded one time of the teaching and learning process. There were two instrumentations used: audio recorder and the field note. Based on data analysis, it was found that the most dominant interaction pattern from classroom discourse was the teacher-student interaction with two-way traffic interaction (64%), and then it is followed by teacher-student interaction with one-way traffic interaction (34%), the multi-way interaction pattern 2%, and none of the student-student interaction pattern found in the interactions of the foor classes of English lesson. This indicates that the teachers mostly spend their teaching and learning process by asking questions to the students with limited interaction in a topic of talk. Students’ responses were seen not so important to involve them to the materials and the process of teaching and learning in the classroom. Therefore, the interaction pattern that mostly appeared was teacher-student interaction with two-way traffic interaction. So it is important for the teacher to realize the importance of the classroom interaction characteristic and to develop her teaching skill and method in delivering teaching materials in the classroom.Keywords: classroom interaction pattern, El Hanafi, English class.